Peningkatan Hasil Belajar Matematika Materi Tanda Waktu Siswa Kelas III SDN Karangsambung 03 Menggunakan Media Jam Tiruan - Sari, Katri Wulan (Didaktika, 2021)
This research was motivated by observations of mathematics learning in third grade of the State Elementary School of Karangsambung 03 in an even semester where many students were less enthusiastic. It was because the teachers applied less varied learning methods. The teachers need to increase student activity and motivation in the mathematics learning process. To attract students, applying artificial clock media could be solutive. This problem was addressed through classroom action research which is carried out through 3 cycles with planning, action, observation, and reflection stages for each stage. The results showed that the application of artificial clock media can improve learning outcomes of time material in third-grade students. This can be seen from the increase in learning outcomes per cycle where in the pre-cycle there were 10 students or 40%, in the first cycle there were 17 students or 68% and in the second cycle, there were 23 students or 92% of students passed the minimum score. This showed that the learning process was carried out following the specified indicators of a minimum score of 70 which 80% of students succeed. The increase also indicated student learning activities per cycle where in the pre-cycle was only 20.25% and in the first cycle was 31.25% increase in the second cycle to 90.62%. Thus, it can be concluded that the use of artificial clock media can improve the learning outcomes of third-grade students at the State Elementary School of Karangsambung 03.